Determination of Estrogens in Milk Samples by Magnetic‐Solid‐Phase Extraction Technique Coupled With High‐Performance Liquid Chromatography. Issue 12 (21st October 2015) - Wang, Juan; Cheng, Chunsheng; Yang, Yaling
Abstract: A magnetic‐solid‐phase extraction method coupled with high‐performance liquid chromatography and diode array detection has been developed for simultaneous determination of 3 estrogens in milk samples. In this work, Fe3 O4 NPs were synthesized by a simple chemical co‐precipitation reaction, and the surface of Fe3 O4 was modified with cetyltrimethyl ammonium bromide (CTAB; designed as Fe3 O4 @CTAB). The synthesized Fe3 O4 @CTAB NPs were characterized by Fourier transformed infrared spectroscopy, scanning electron microscopy, and transmission electron microscope. Fe3 O4 @CTAB NPs have high binding affinity toward estrone (E1), 17β‐estradiol (17β‐E2), and diethylstilbestrol (DES). Fe3 O4 @CTAB NPs can be easily separated from sample solutions using an external magnet due to the high super‐paramagnetic property. The separation, preconcentration procedure is fast and will be completed in 2 min. Estrogens linear dynamic ranges were achieved in the range of 10 to 1000 ng/mL with regression coefficients ( R 2 ) higher than 0.9992. The limits of detection were between 0.26 and 0.61 ng/mL. Parameters influencing the recoveries were investigated and optimized. The proposed method was used for the determination of E1, 17β‐E2, and DES in milk samples, and recoveries were ranged from 91.3% to 105.0%, with the relative standard deviations in the range of 2.7% to 4.0%.